The Effect of Profitability, Leverage, and Company Size on Company Value: Empirical Study on Manufacturing Companies in the Food and Beverage Subsector Listed on the Indonesia Stock Exchange - Kristom Eko Kanika; Rachmat Arief (CNPLUS Publisher, 2025)
This study aims to examine and analyze the effect of profitability, leverage, and firm size on firm value in the food and beverage manufacturing sub-sector companies listed on the Indonesia Stock Exchange from 2021 to 2024. The sample was selected using a purposive sampling technique, resulting in 47 food and beverage companies listed on the Indonesia Stock Exchange during the 2021-2024 period. The data analysis technique employed was multiple linear regression analysis using SPSS software. The results indicate that, partially, profitability has a positive and significant effect on firm value, suggesting that profit-earning efficiency serves as a positive signal for investors. Conversely, leverage and firm size do not have a significant effect on firm value. Simultaneously, all three variables profitability, leverage, and firm size significantly influence firm value.